2016
DOI: 10.1111/jfpe.12332
|View full text |Cite
|
Sign up to set email alerts
|

Kefir Grain Biomass Production: Influence of Different Culturing Conditions and Examination of Growth Kinetic Models

Abstract: In this study, kefir grain biomass growth was investigated in whey enriched with some additives such as yoghurt, milk, glucose, sucrose, yeast extract and carob extract. The fermentation experiments were carried out at 27°C for 10 days by refreshing the cultivation media at the end of each 24 h fermentation period. Maximum and minimum biomass increases were obtained as 1,438 and 836% in whey enriched with 5% (w/v) yeast extract and 10% (v/v) carob extract, respectively. Kefir biomass increase and fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
2
15
0
7
Order By: Relevance
“…Apar studied the effects of temperature and initial Kefir concentration on biomass production and fermentation. The results showed that the optimal temperature for growth of Kefir biomass and the initial Kefir particle concentration were 27°C and 5%, respectively (Apar, Demirhan, Özel, & Özbek, ). Bensmira studied the effects of fermentation conditions and homogenization pressure on Kefir rheology (Bensmira, Nsabimana, & Jiang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Apar studied the effects of temperature and initial Kefir concentration on biomass production and fermentation. The results showed that the optimal temperature for growth of Kefir biomass and the initial Kefir particle concentration were 27°C and 5%, respectively (Apar, Demirhan, Özel, & Özbek, ). Bensmira studied the effects of fermentation conditions and homogenization pressure on Kefir rheology (Bensmira, Nsabimana, & Jiang, ).…”
Section: Discussionmentioning
confidence: 99%
“…The removal of the dyes by living and inactivated grains drastically decreased to 11.38% and 1.03% as pH was increased to 8. Kefir is an acidic, viscous, lightly carbonated dairy beverage and it is known that the living kefir grains are stable in a wide pH range, since during the fermentation the pH of the milk decrease from 6.8 up to 3.3 [30]. As the decrease in dye removal efficiency was also observed with nonliving kefir grains it can be stated that these decrease is not related with the inactivation of the active microflora of kefir grains.…”
Section: Optimization Of Biosorptionmentioning
confidence: 99%
“…The kefir grains (starter culture for the probiotic fermented milk drink kefir) are small, gelatinous white/ yellow irregularly shaped masses consist of live bacteria (lactic acid bacteria of the genus Lactobacillus, Lactococcus, Leuconostoc and acetic acid bacteria) and yeasts (consist of Kluyveromyces, Candida, Saccharomyces and Pichia) in a slimy polysaccharide matrix and are responsible for lactic acid and alcoholic fermentation. Traditional production of kefir drink involves inoculation of milk with a variable amount of grains and fermentation [30,31]. During the fermentation kefir grains increases and in a few day the amount get excess for a specified amount of beverage production and require to remove the excess amount in order to standardization of the product.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations